Getting Lucky: The Long-Term Consequences of Exam Luck - Fanny Landaud; Éric Maurin; Barton Willage; Alexander L.P. Willén (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper studies the impact of exam luck on individuals' education and labor market success. We leverage unique features of the Norwegian education system that produce random variation in the content of the exams taken by students at the end of high school. Lucky students take exams in subjects they are better at, and we show that this generates significant improvements in both their high school GPA and diploma probability. Subsequently, exam luck generates substantial and persistent wage differentials across otherwise identical individuals. These luck-induced wage effects are of a similar magnitude as those generated by well-known education inputs, such as parental education and teacher quality.
Keywords: D63; H52; I21; I23; I24; I26; J24; J31; 330; luck; fairness; wage differentials; returns to education; high-stakes exams